Affectedness: Observations on Turkish - Pınar İBE AKCAN (Dilbilim Araştırmaları Dergisi)
This study aims to describe the linguistic concept of affectedness, which is mostly intuitively but not clearly defined, though it has been used frequently in the related literature in Turkish. It is referred to in many studies on syntax, semantics, and pragmatics in Turkish, yet it has not been studied on its own and is not comprehensively defined. The study analyzes this semantic primitive using constructed and natural language data in Turkish. With that aim, the literature on different languages and proposed diagnostic tests will first be reviewed, and then the question of which verbs can be the affecting ones in Turkish will be addressed within the scope of English classifications. Subsequently, combinations of Turkish verbs and their case marked arguments will be overviewed. The typical potentially affecting transitive action verb kır- , the typical potentially affecting transitive psychological verb üz-, and the postpositions üst- and üzeri- in Turkish will be examined in terms of affectedness in natural language data. The main purpose of the study is to clear the ground for further studies in Turkish that will potentially use this semantic primitive.